Use of human intravenous immunoglobulin in lower motor neuron syndromes. Issue 1 (1st July 1999) - Ellis, C M; Leary, S; Payan, J; Shaw, C; Hu, M; O'Brien, M; Leigh, P N
Abstract : OBJECTIVE: To determine whether patients with the clinical phenotype of multifocal motor neuropathy but without the electrophysiological criteria for conduction block would respond to intravenous immunoglobulin (IVIg). METHODS: Ten patients were selected with a slowly progressive, asymmetric, lower motor neuron disorder, and were treated prospectively with IVIg at a dose of 2g/kg over 5 days. All subjects had neurophysiological testing to look for evidence of conduction block before treatment. Muscle strength was assessed by MRC grades and hand held myometry, measuring pinch and grip strength. A 20% increase in both pinch and grip myometry was considered a positive response. RESULTS: In no patient was conduction block detected. Four of the 10 patients showed a positive response to IVIg, with the best response occurring in two patients who presented with weakness but without severe muscle wasting. Three of the four responders have continued to receive IVIg for a mean period of 17 months (range 15–24 months), with continued effect. The response to IVIg was not related to the presence of anti-GM1 antiganglioside antibodies, but responders had a selective pattern of muscle weakness and normal (>90% predicted) vital capacity. CONCLUSION: The findings suggest that a course of IVIg should be considered in patients with the clinical phenotype of multifocal motor neuropathy but without neurophysiological evidence of conduction block.